Hazardous effects of silver nanoparticles for primary producers in transitional water systems: The case of the seaweed Ulva rigida C. Agardh. (October 2019) - Sfriso, Andrea Augusto; Mistri, Michele; Munari, Cristina; Moro, Isabella; Wahsha, Mohammad; Sfriso, Adriano; Juhmani, Abdul-Salam
Abstract: The acute toxicity of citrate capped silver nanoparticles (AgNP) and silver nitrate was evaluated on the marine macroalga Ulva rigida C. Agardh (1823). Silver bioaccumulation, ultrastructural chloroplast damages verified by TEM microscopy, inhibition of primary production, neutral lipid production and oxidative stress were observed after 24 h of exposure to AgNP. The toxic effects of silver nitrate in artificial seawater started from a concentration of 0.05 ppm and was more toxic than AgNP that produced effects from a concentration of 0.1 ppm. However only AgNP induced lipid peroxidation in U. rigida . The addition of natural organic and inorganic ligands, represented by transparent exopolymer particles (TEP) and clay, drastically reduced AgNP acute toxicity in a ratio AgNP:ligand of 1:100 and 1:200, respectively. The findings suggest a marked toxicity of Ag on marine macroalgae which however should be mitigated by the high natural ligand concentrations of the transitional environments. Highlights: The toxic effect of AgNP on Ulva was detected at low concentration of 0.1 ppm. Ag was accumulated in the tissues of Ulva and resulted in chloroplast disruption. Natural organic and inorganic ligands reduced the AgNP acute toxicity.